The State‐Level Impacts of Enforcing Sales Taxes for E‐retail Purchases. (22nd July 2015) - Conroy, Tessa; Cutler, Harvey; Weiler, Stephan
Abstract: The Marketplace Fairness Act (S. 743) recently passed by the U.S. Senate may portend a national move toward states imposing sales taxes for business‐to‐consumer e‐retail purchases. While much of the policy debate surrounding this question has focused on trade creation versus diversion, there are likely distinct compositional effects at the state level, which will affect both economic activity and tax revenue. Consumers are clearly hurt by an online sales tax. However, such a policy would seemingly benefit state tax coffers, as well as traditional brick‐and‐mortar retailers and their employees. This paper uses a computable general equilibrium model approach to get a better understanding of the state‐level income, employment, and tax revenue effects of such a policy shift, in particular the likely tradeoffs between these three traditional economic targets across reasonable ranges of price elasticities.